Case study: SERAC vs. Nigeria examining the role of international law in supporting social movement goals - Williams, Owen (AUC Knowledge Fountain, 2011)
The struggle to curtail environmental degradation and enhance local control over resource use in the Niger Delta region provides a context to examine the role of international human rights law in supporting the goals of social movements. Oil exploitation has done incredible damage to the Niger Delta since the mid 20th century. Regular oil spills and constant gas-flaring have wreaked havoc on the ecosystem and destroyed the livelihoods and lifestyles of the peoples that inhabit the Delta, engendering a variety of resistance from these peoples. The resistance to oil exploitation in the Delta included both the ongoing local social movement for autonomy and environmental control, and a groundbreaking case before the African Commission on Human and Peoples Rights, SERAC V. NIGERIA . The SERAC case led to a communication in which the Commission enumerated environmental and peoples rights in new ways and for the first time insisted on state responsibility for the right to environment. The case is widely commented on for opening new ground in environmental and human rights activism. The coincidence of the social movement in the Delta and the SERAC case allows for a study examining the usefulness of international human rights law in supporting the goals of social movement activism. Following a survey of the history of oil in the Delta, the SERAC case, and the social movement, the present work will argue that in this case and similar struggles, international human rights law has a limited role to play supporting a broad, local, ongoing social movement standing in complex relation to the state, holding it responsible and recognizing its limitations. This framing reduces the possible limitations of the use of human rights law. Anti-black global biases, replicated in human rights, undermine international solidarity in favor of a local/regional focus and language of legal disputes limits articulation of social movement goals requiring a broad ongoing movement to push full aspirations of peoples for autonomy and local environmental control.